Currency crises in emerging markets: Capital flows and herding behaviour - Tuomas Komulainen (Bank of Finland, Institute for Economies in Transition (BOFIT), 2001)
This study shows that due to herding behaviour and possible capital outflows, emerging market countries are vulnerable to multiple equilibria situations and currency crises.It uses a model by Jeanne (1997), where currency crises can be formed by multiple equilibria and self-fulfilling expectations.We determine the country fundamentals according to balance of payments approach.In this study we introduce capital flows, which depend from crisis probability, into the model.The capital flows are further assumed to follow herding behaviour, which produces a reason and mechanism for the large capital outflows witnessed during the recent crises. The range of country fundamentals, where self-fulfilling crises are possible, is now larger than without capital flows and herding behaviour.Consequently, the country fundamentals have to be better, if the country wants to stay totally out of crises.The model further points out lender interdependence as one shortcoming in the current structure of international capital markets.An empirical application of the model to the Mexican and Asian crises shows that when the possible capital outflows are included, the fundamentals of most emerging market countries were inside the range of multiple equilibria in 1994 and 1996, and so self-fulfilling crises were possible.
URN:NBN:fi:bof-201408071959
Keywords: 330